Perhitungan Pengendalian Persediaan Fast Moving Spare Part Dengan Metode Min-Max Stock - Khairunnisa, Alyaa Sekar; Prihadianto, Braam Delfian (Infotekmesin, 2023)
Maintenance is an effort to maintain a heavy equipment unit to keep it in good condition. One of the techniques to maintain unit performance is by carrying out maintenance management which is a combination of various activities such as monitoring, scheduling, repairing, and inventory control. One part of maintenance management is inventory management which aims to ensure the availability of spare parts in the warehouse so that it can increase the efficiency of maintenance time. The purpose of this study is to calculate the supply of fast-moving spare parts, especially oil filters and diesel filters using the Min-Max Stock method at PT Armada Hada Graha Basecamp Kelontong. The research used a comparative quantitative method utilizing spare parts usage data from January to March 2022 and inventory stock data on March 2022. From the calculation results it can be concluded that the percentage of filter inventory between the minimum and maximum stock values ​​is 7%. It happens due to several factors, namely, materials, methods, machines, and the environment.